Transformational Leadership Strategies: Enhancing Teacher Leadership in Schools - Nurfahila, Shielsilia Amara; Yuliana, Lia (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study investigates the strategies employed by principals to foster teacher leadership through a transformational leadership approach in a school in East Lombok. A qualitative case study method was utilized, involving semi-structured interviews and document analysis with four teachers and one principal as participants. The findings reveal three key strategies implemented by the principal: conducting regular meetings to address educational challenges and share best practices, facilitating teacher professional development through workshops and training, and actively involving teachers in decision-making processes. These strategies align with transformational leadership dimensions, including idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The results underscore the significant role of principals as transformational leaders in promoting teacher leadership, enhancing collaboration, and fostering a positive school culture. This study highlights the practical implications for principals to adopt transformational leadership practices to optimize teacher potential and improve overall educational outcomes. Further research is recommended to explore the challenges of implementing teacher leadership in diverse educational settings and to assess its impact on long-term school performance.